A comparative pattern of lectin-binding in the endometrial glands of the uterus and placenta of healthy buffaloes and bovines at early gestation - Caspe, Sergio Gastón (2021)
Fil: Caspe, Sergio Gastón. Instituto Nacional de Tecnología Agropecuaria. Experimental Station Mercedes. Laboratory of Pathology; Argentina.